2017
DOI: 10.1111/idh.12290
|View full text |Cite
|
Sign up to set email alerts
|

Supportive periodontal treatment: Pocket depth changes and tooth loss

Abstract: This study indicates that with regard to bleeding on probing and probing pocket depth, patients receiving supportive periodontal treatment maintain their periodontal condition. However, in this group of adherent maintenance patients, tooth loss was most prevalent for molar teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…site‐based). Of the 33 studies included, seven did not report statistical comparisons of patient‐ or tooth‐related risk factors (De Wet et al, 2018; Graetz et al, 2011; Hirschfeld & Wasserman, 1978; McFall, 1982; McLeod et al, 1998; Papantonopoulos, 2004; Wood et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…site‐based). Of the 33 studies included, seven did not report statistical comparisons of patient‐ or tooth‐related risk factors (De Wet et al, 2018; Graetz et al, 2011; Hirschfeld & Wasserman, 1978; McFall, 1982; McLeod et al, 1998; Papantonopoulos, 2004; Wood et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation of this analysis could be its generalizability since the findings were obtained from a database from a clinic that is specialized in periodontal therapy. Numerous studies have demonstrated the beneficial effect of periodontal treatment and maintenance in this specific private periodontal clinic 6,28 . It is known from research that patients in private periodontal clinics compared to those treated in an academic setting show significant better stability of the periodontal condition based on less progression of periodontitis and tooth loss 51 .…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, safe to state that the annual TL found can be considered to be acceptable, which is an indication of periodontal stability. However, the implications of TL are wide and the impact on the patient's quality of life is immeasurable 2,3,6,27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Host-microbial interactions are key factors in the pathogenesis of periodontitis, while certain risk factors including smoking, poor oral hygiene, and diabetes are likely to increase host susceptibility [ 17 , 18 ]. Clinical periodontal status parameters, including scores of supragingival plaque, bleeding, suppuration and probing depth as well as tissue appearance can be useful indicators of periodontal disease presence and progression [ 19 ]. Identifying an individual's risk factors could further enhance evaluation and monitoring of the susceptibility for disease progression, thereby optimizing treatment strategies [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%